An intervention using the Parenting Toolkit "Children—What does it involve?" and the Real‐Care‐Baby simulator among students with intellectual disability—A feasibility study. Issue 2 (23rd October 2018) - Janeslätt, Gunnel; Larsson, Margareta; Wickström, Maria; Springer, Lydia; Höglund, Berit
Abstract: Background: There is limited knowledge about how young people with intellectual disability can be facilitated in their process of deciding about parenthood. This study aimed to evaluate the feasibility of an upcoming trial to evaluate an intervention using the Toolkit "Children—what does it involve?" and the "Real‐Care‐Baby" (RCB) simulator among students with intellectual disability. Methods: Six students with intellectual disability participated in an intervention with eight educational sessions and a 3‐day caring session with the RCB simulator. Data were collected with questionnaires and interviews. Results: The study showed that it is possible to evaluate an intervention using these instruments among students with intellectual disability in order to provide them with further insights about parenthood. Conclusion: It is feasible to evaluate the Toolkit and the RCB in a cluster‐randomized study and that such a study could add to our knowledge about possible intervention strategies regarding reproduction and parenting among students with intellectual disability.